Meningkatkan Kepercayaan Diri Dalam Menyampaikan Pendapat Melalui Layanan Bimbingan Kelompok pada Siswa Kelas II SDN 105367 Desa Karang Anyar - Syarqawi, Ahmad; Ary Rambe,, Afghan Bai Asy; Tanjung, Asbih Fahrezi; Rezeki, Leni Sri; Neng Dewi, Suharti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The research objective was to find out the results of implementing group guidance services on increasing the self-confidence of elementary school children. 105367 Karang Anyar Village. Implementation of research using descriptive research mode with a qualitative approach and a case study approach. Then the process of collecting data from this study used observation techniques, interviews, and documentation studies, which used Miles and Huberman's analysis, namely data reduction, data presentation and drawing conclusions. The research subjects were students at SDN. 105367 Karang Anyar Village. The results of the research on the self-confidence of class II students at SDN 105367 in Karang Anyar Village increased after group counseling was carried out. This can be seen from changes in attitudes and behavior shown by class II students at SDN. 105367 Karang Anyar village from stage to stage, whose attitude and behavior initially preferred to be silent and passive changed to being active and braver in giving responses in the sense of being more confident after implementing group guidance. Keywords: Group Guidance, Improving, Self-Confidence